Zygomaticotemporal nerve and auriculotemporal nerve block: a vicious cycle breaker for cluster headache pain - Mallikarjuna, Swathi; Gupta, Priyanka; Tiwari, Ashutosh; Kumar, Mritunjai (Nepal Journal of Neuroscience, 2024)
Nerve blocks are the reasonable choice for cluster headache and other nerve associated pain. Blocks used in cluster headache included in literature are Occipital nerve block and Sphenopalatine ganglion block. To our knowledge, the effectiveness of zygomaticotemporal nerve and auriculotemporal nerve block with bupivacaine for the treatment of cluster headache has not been reported. Here we present a case report of 74-year-old male with cluster headache nonresponsive to oxygen therapy, subcutaneous sumatriptan, zolmitriptan spray and other medications. Patient got relieved by the zygomaticotemporal nerve and auriculotemporal nerve block and started responding to the same acute pain management.